Microstructure Evaluation of Ductile Cast Iron and Numerical Modal Analysis - Kovacikova, Petra; Vavro, Jan; Vavro, Jan; Dubec, Andrej (Manufacturing Technology Journal, 2018)
This work is closely connected with the evaluation of the microstructure of the cast iron with the spherical shape of graphite. The given work is mainly focused on mechanical properties, chemical composition and microstructure, which are important to be known as an input parameters for computational modelling and numerical analysis. The external factors, influencing the measure of the mechanical damping, include the measure of the mechanical loading, loading frequency and temperature. These factors have the influence on the process of the mechanical energy distribution in materials. Eigenshapes as well as eifenfreguencies were investigated by modal analysis using finite element method (FEM).
Keywords: cast iron; microstructure; mechanical properties; modal analysis